The Contentious Role of Tourism in Disaster Response and Recovery in Vanuatu - Neef, Andreas (Frontiers in Earth Science, 2021)
Tourism is a key contributor to the economy of the Pacific Island country Vanuatu. Yet many Ni-Vanuatu have seen their access to natural resources lost or reduced as a consequence of foreign investment in the tourism industry and associated land leases, while few community members found secure employment in the tourism sector to compensate for those losses. The tension between externally driven tourism development and local resource access has been exacerbated in the aftermath of 2015 Tropical Cyclone Pam which caused extensive damage both to the tourism industry and local communities. Employing a tourism-disaster-conflict nexus lens and drawing on semi-structured interviews with hotel managers, research conversations with hotel staff and community members, and focus group discussions with community leaders, this study examines how the tourism sector has impacted post-disaster response and recovery, particularly in terms of land relations and rural livelihoods. Findings suggest that tourism can be a double-edged sword for disaster-prone communities. While resorts play an important role as first responders, their contributions to post-disaster recovery processes remain ambiguous and marred by tensions between expatriate investors and indigenous Ni-Vanuatu people. These findings also hold lessons for the tourism crisis triggered by the COVID-19 pandemic in the South Pacific and elsewhere.